Uji radioimun untuk progesteron - G Wanananda; D Sastradipradja; P Paridjo (Hemera Zoa, 1983)
A radioimmunoassay (RIA) for progesterone plasma of various animal species had been applied and validated in our laboratory. The method used antisera against 11 alpha hydroxy progesterone raised in goats (donated by Dr. L.E Edqvist, Sweden) in a 1:2000 dilution. A sensitivity of 10 pg/ml was obtained based on the readings for this concentration which was statistically different from a zeroconcentration (p